Precision Medicine in the Era of Genetic Testing: Microsatellite Instability Evolved - Ioffe, Dina; McSweeny, Michelle; Hall, Michael J. (Clinics in Colon and Rectal Surgery, 2023)
The recognized importance of microsatellite instability (MSI) in cancer has evolved considerably in the past 30 years. From its beginnings as a molecular predictor for Lynch syndrome, MSI first transitioned to a universal screening test in all colorectal and endometrial cancers, substantially increasing the identification of patients with Lynch syndrome among cancer patients. More recently, MSI has been shown to be a powerful biomarker of response to immune checkpoint blockade therapy across a diversity of tumor types, and in 2017 was granted Food and Drug Administration approval as the first tumor histology-agnostic biomarker for a cancer therapy. Focusing on colorectal cancer specifically, immune checkpoint blockade therapy has been shown to be highly effective in the treatment of both MSI-high (MSI-H) colon and rectal cancer, with data increasingly suggesting an early role for immune checkpoint blockade therapy in MSI-H colorectal tumors in the neoadjuvant setting, with the potential to avoid more toxic and morbid approaches using traditional chemotherapy, radiation therapy, and surgery. The success of MSI as an immune checkpoint blockade target has inspired ongoing vigorous research to identify new similar targets for immune checkpoint blockade therapy that may help to one day expand the reach of this revolutionary cancer therapy to a wider swath of patients and indications.
Keywords: microsatellite instability; colorectal cancer; immune checkpoint blockade